MORPHOLOGICAL AND METRIC CHANGES OF THE GLANDULAR APPARATUS OF THE RAT STOMACH FUNDUS UNDER THE EFFECT OF A COMPLEX OF FOOD ADDITIVES - Yeroshenko G.А.; Yachmin А.І.; Shevchenko, K.V.; О. Д Лисаченко; Riabushko, O.B.; Sokolenko, V.M.; Sharlai, N.M. (World of Medicine and Biology, 2022)
The paper presents the data of morphometric and histological examination in the complex action of food additives on the glandular apparatus of the stomach fundus. It was found that the complex action of dietary supplements of sodium nitrite, sodium glutamate and Ponceau 4R leads to changes in morphometric parameters of the fundus glands with the development of a complex reaction, followed by inflammatory reaction and edema. Reconstructive reactions aimed at neutralizing the alternative factor and restoring the morphofunctional state of the glands of the stomach fundus do not lead to complete recovery of structural components due to the predominance of constant negative stimuli with dystophic changes, expressed by changes in morphometric parameters and morphological structure.